Dynamic characteristics of iron-cored magnets using high-T-c superconductors - ElAbbar, A; Goodall, R; MacLeod, C; Campbell, A; Jenkins, R; Jones, H (1995)
This paper describes the dynamic characteristics of high-T-c superconducting magnets with an iron core under different operating conditions. The main objective of this work is to understand the limits of controllability of these magnets for use in controlled applications such as electromagnetic suspensions (EMS) and bearings. Experimental results obtained using laminated and solid iron cores indicated that the ac losses are dominated by eddy currents in the iron cores, and the losses in the superconductor are relatively insignificant.